IMPLEMENTASI ETIKA BISNIS ISLAM DI INDUSTRI PENGECORAN LOGAM BATUR, CEPER, KLATEN - Santosa Pambudi, Dwi (Program Studi Ekonomi Syariah Universitas Yudharta Pasuruan, 2017)
Business activities that ignore the ethical dimension are in fact detrimental to society, two entities that should be integrated into a single entity. In Batur, Ceper, Klaten most of the population are metal casting entrepreneurs, the dynamics of business activity is very tight, the whole population is Muslim, many traditional pesantren so that business ethics becomes a serious concern. The phenomenon that is happening. First, there is a businessman experiencing rapid growth of business. Secondly, business entrepreneurs decreased business activity and even stalled. Researchers use field research methods or (Research field), with descriptive nature. Technique of collecting data by interview and observation. To analyze the data, use qualitative analysis in an inductive way. The result of the research shows that Islam considers business not merely to gain material advantage, but also to achieve the goal of the essence of humanity (Khalifah Allah). In such alignment, Islam provides a paradigm building in business. Implementation of Islamic business ethics of metal foundry by providing correct product information, honest, giving guarantee and comfort to consumer. So many million attention to the people of the surrounding community by alleviating poverty and paying zakat.